Les limites du discours économique sur la publicité - Chébat, Jean-Charles; Lapointe, Alain (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractIt is often assumed that the negative impact of advertising is the basis from which economic studies in this area are to be undertaken. The authors state that the evidence supporting such a claim is far from obvious. In fact, the suggestion brought forth is that this assumption may be faulty. Specific areas of inquiry are suggested such as the cost of advertising in relation to marketing and manufacturing costs as well as the impact of advertising on GNP. The authors point out that from a demand analysis perspective, the eternal diseconomies in consumption due to advertising as claimed and condemned by economists, is really the result of the consumer's decision making process in the market place. The economists fail to take into account all of the social and psychological forces which impact on consumer behavior. Finally, the authors state that from a supply analysis orientation, no conclusion link has been found between advertising, industrial concentration and market power.